Truth-conditional pragmatics - d (Oxford : Oxford University Press, 2010)
Recanati argues against the traditional understanding of the semantics/pragmatics divide. Through half a dozen case studies he shows that 'pragmatic modulation' interacts with the grammar-driven process of semantic composition. As a result what an utterance says cannot be neatly separated from what the speaker means.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Dec. 17, 2010).
Keywords: Pragmatics; Speech acts (Linguistics); Pragmatics -- Case studies; Speech acts (Linguistics) -- Case studies